Prognostic value of the hemodynamic gain index in different groups of patients undergoing cardiopulmonary exercise stress testing. (14th October 2021) - Chaikijurajai, T; Wu, Y; Grodin, J L; Harb, S; Jaber, W; Tang, W H W
Abstract: Background: A novel hemodynamic parameter obtained from the cardiopulmonary exercise testing (CPET), the hemodynamic gain index (HGI), was developed and shown to be a strong independent predictor of all-cause mortality in a large male cohort. The HGI also strongly correlates with exercise parameters such as peak oxygen consumption and metabolic equivalents (METs). However, prognostic implications of the HGI have not been externally validated with subgroup analyses based on sex, heart failure (HF), coronary artery disease (CAD) and the use of beta-blockers. Purpose: We aimed to validate the prognostic value of the HGI in men, women, and patients with and without HF, CAD, and beta-blocker use. Methods: We identified 126, 356 consecutive patients undergoing treadmill exercise testing for symptom evaluation between 1/1/1991–02/27/2015. HGI was calculated using the formula, [(SBPpeak x HRpeak) − (SBPrest x HRrest)] / (SBPrest x HRrest). Univariable and multivariable cox regression models were used to determine the associations between the HGI stratified by quartiles and all-cause mortality at 10 years with adjustment for cardiovascular risk factors (age, sex, diabetes, hypertension, dyslipidemia, chronic kidney disease, smoking status and body mass index) and exercise testing parameters (chronotropic reserve index, METs, abnormal heart rate recovery, and total exercise time). Results: In our study cohort, mean age was 53.5±12.6 years. There were 74, 724 (59.1%) male, 5, 940 (4.7%) HF, 21, 123 (16.7%) CAD, and 30, 568 (24.2%) beta-blocker-using patients. During the mean follow up of 8.7 years, 9, 929 (7.9%) died. Mean HGI was 2.0±1.2 bpm/mmHg. Lower HGI was associated with all-cause mortality in the entire cohort (Figure 1A, log rank p<0.001). After adjustment for the covariates, the lowest quartile of the HGI was independently associated with all-cause mortality in subgroups of men, women, and patients with and without HF, CAD, and beta-blocker use (Figure 1B, all p≤0.001) compared with the highest quartile of the HGI. Conclusions: HGI is an independent predictor of long-term mortality after adjusted for traditional cardiovascular risk factors, and exercise performance across patient subgroups. FUNDunding Acknowledgement: Type of funding sources: None.